Using Jigsaw Technique to Identify and Develop Paragraph Elements at The Fourth Semester Students of UKI-Toraja - Aris Kaban Sendana (Teaching English as a Foreign Language Overseas Journal, 2015)
The objectives of this research are (1) to find out the effects of jigsaw technique on students’ ability in writing the paragraph elements at the fourth semester students of UKI-Toraja, (2) to find out whether the students are interested in the teaching of paragraph elements using jigsaw technique. This research employed cluster random sampling technique. It used two groups, one received treatment using Jigsaw Technique and the other group received the conventional way from the Lecturer who taught writing two in that semester. The subjects of this research were two classes, class B (22) as experimental group and class C (22) as control group. The data of this research was collected through writing test and questionnaire. The results of the research revealed that (1) using Jigsaw Technique affects the ability of the fourth semester students of UKIToraja in writing the elements of a good paragraph. (2) The interest of class B as experimental group of the fourth semester students of UKI-Toraja in writing the elements of a good paragraph showed a great positive.